ALFONSO FANJUL PERAZA, Deserts Stories & Bedouin Legends. Charleston, Pigafetta Collection, 2015. 122 pp. ISBN 978–84–606–6277–8. € 10 - Argüelles Alvarez, Patricia (2016)
Fil: Argüelles Álvarez, Patricia. Universidad de Educación Nacional a Distancia; España